The Relationship between Female Directors and Earnings Quality of Chinese Listed Companies - Wang, Yihan (2019)
At present, earnings management has been the focus of theoretical and practical circles. Imperfect corporate governance is a common phenomenon in China. Scholars constantly explore various methods to solve corporate governance problems, which is also an important reason for this paper to conduct research on earnings management. This paper takes Chinese listed companies as research objects to study the influence of female directors on earnings management. The results show that: first, female directors can significantly inhibit corporate earnings management; Second, when a company employs two or more women directors, the earnings quality of listed companies can be significantly improved. Third, women directors have upward and downward motives in manipulating earnings management. Then, this paper puts forward the following suggestions: it is necessary for the state to guide enterprises to improve talent training and internal promotion mechanism, attach more attention to the training of women employees, and promote excellent women employees to enrich enterprise management. Secondly, enterprises should be guided to increase the proportion of female directors on the board, optimize the gender structure of directors and give full play to the influence of women independent directors, so as to curb earnings management and improve the quality of financial reports. Keywords: Female Director; Earnings Quality; Earnings Management